Removal of Pb(II) from Aqueous Solution by Ceramsite Prepared from Isfahan Bentonite and γ-Alumina - Mobasherpour, Iman; Javaherai, Masomeh; Salahi, Esmail; Ebrahimi, Mohsen; Ashrafi, Zahra; Orooji, Yasin (Видавництво Львівської політехніки, 2021)
Досліджено процес видалення свинцю з водних розчинів за допомогою нанокомпозитного абсорбенту бентоніт/γ-оксид алюмінію. Характеристику нового абсорбентупроведено з використанням рентгенівської дифрактометрії, Фур‘є спектороскопіїта скануючої електронної мікроскопії. Оптимізацію процесу проведено з використанням методології поверхні відгуку (RSM) та центрального композиційногоплану експерименту. Досліджено вплив початкової концентрації Pb(II), дози адсорбенту та композиційного відсотку на ступінь видалення Pb(II) та адсорбційну здатність. За ізотермічними моделями Лангмюра, Фрейндліха та Дубініна-Радушкевича досліджено процес адсорбції. Встановлено, що ізотермічна модель Фрейндліха підходить краще у порівнянні з іншими моделями.

Removal of lead from aqueous solutions was studied using nanocomposite absorbent of bentonite/galumina. The novel absorbent was characterized using XRD, FT-IR and SEM-EDX. Absorption process optimization using response surface methodology (RSM) and experimental design was performed with central composite design technique. The effects of Pb(II) initial concentration, adsorbent dosage, and composite percentage on Pb(II) removal percentage and adsorption capacity were examined. The adsorption capacity of 166.559 mg/g and removal % of 82.9887 with desirability equal to 0.763 were obtained for optimal initial concentration of 200 mg·l-1, adsorbent dosage of 0.5 mg·l-1, and composite percentage of 7.08 % determined using RSM design. The equilibrium adsorption data were investigated by Langmuir, Freundlich and Dubinin-Radushkevich isotherm models. It was found that Freundlich isotherm model fits better compared with other models.
Видалення Pb(II) з водного розчину керамзіту, приготованого із суміші ісфаханського бентоніту та γ-оксиду алюмінію
Keywords: ступінь видалення; Pb(II); бентоніт/γоксид алюмінію; методологія поверхні відгуку; removal percentage; Pb(II); bentonite/γalumina; response surface methodolog